HIF-1α Regulates Glucocorticoid-Induced Osteoporosis Through PDK1/AKT/mTOR Signaling Pathway - Xu, Wen-Ning; Zheng, Huo-Liang; Yang, Run-Ze; Jiang, Lei-Sheng; Jiang, Sheng-Dan (Frontiers in Endocrinology, 2020)
Long-term and high dose glucocorticoid treatment can cause decreased viability and function of osteoblasts, which leads to osteoporosis and osteonecrosis. In this study, we investigated the role and mechanism of action of HIF-1α in glucocorticoid-induced osteogenic inhibition in MC3T3-E1 cells. Our results showed that HIF-1α protein expression was reduced when MC3T3-E1 cells were exposed to dexamethasone (Dex) at varying concentrations ranging from 10-9 M to 10-6 M. PDK1 expression was also decreased in MC3T3-E1 cells after dexamethasone treatment. MC3T3-E1 cells when treated with the glucocorticoid receptor antagonist RU486 along with dexamethasone showed enhanced HIF-1α expression . In addition, upregulated expression of HIF-1α was capable of promoting the osteogenic ability of MC3T3-E1 cells and PDK1 expression. However, the HIF-1α antagonist 2-methoxyestradiol (2-ME) had a reverse effect in MC3T3-E1 cells exposed to dexamethasone. Furthermore, the PDK1 antagonist dichloroacetate could repress the osteogenic ability of MC3T3-E1 cells, although HIF-1α was upregulated when transfected with adenovirus-HIF-1α construct . The PDK1 agonist PS48 was able to promote the osteogenic ability of MC3T3-E1 cells treated with dexamethasone. Importantly, the protein levels of p-AKT and p-mTOR were increased in MC3T3-E1 cells treated with dexamethasone after PS48 treatment. In vivo, the PDK1 agonist PS48 could maintain the bone mass of mice treated with dexamethasone. This study provides a new understanding of the mechanism of glucocorticoid-induced osteoporosis.